Description of two tadpoles of Malagasy treefrogs, Spinomantis sp. aff. peraccae and Spinomantis tavaratra (Anura: Mantellidae) - Ndriantsoa, Serge Herilala; Randrianiaina, Roger-Daniel; Ravoahangimalala, Olga Ramilijaona; Vences, Miguel; Glos, Julian (Zootaxa, 2012)
The aim of this study is to present morphological descriptions of the tadpoles of two species of Malagasy treefrogs of the genus Spinomantis (Anura: Mantellidae). The first of these, Spinomantis sp. aff. peraccae, from Ambohitantely is an unconfirmed candidate species (not included in Vieites et al. 2009) of which no adult specimen was collected so far but which is distinguished by a substantial genetic divergence of 6% to S. peraccae, Genbank accession AY848415, from Antoetra in the 16S rRNA gene. This candidate species is thus far taxonomically undescribed, but describing its tadpole contributes to the understanding of larval diversity in the genus Spinomantis and might prove to be important for a future revision of the S. peraccae complex, once that the larvae of S. peraccae and other related candidate species from northern Madagascar become known.